2020
DOI: 10.1021/acsomega.9b03605
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Elemental Mercury from Flue Gas Using Cobalt-Containing Biomaterial Carbon Prepared from Contaminated Iris sibirica Biomass

Abstract: Iris sibirica biomass (ISBM) used for cobalt (Co) pollution remediation was prepared by one-step pyrolysis and employed to remove elemental mercury (Hg0) from flue gas. Results showed that the ISBM pyrolyzed at 700 °C (ISBM700) exhibited good Hg0 removal performance (about 86%) at 150 °C. The existence of NO and O2 facilitated the removal of Hg0, while SO2 and water vapor inhibited it. Characterization analysis (including N2 adsorption–desorption, X-ray diffraction, scanning electron microscopy, X-ray photoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The biomass valorization depends both on plant species used, type of pollutant and its concentration in plants (Vidican et al, 2020). Recent evidence emerged that I. sibirica Cobalt-rich biomass resulting from phytoremediation could be used in the domain of adsorption catalysis to remove Hg from coal combustion flue gas with highly promising industrial applications (Li et al, 2020;Wang et al, 2020). In this sense, results showed that after pyrolysis at 700°C, I. sibirica biochar achieved Hg removal efficiency of 85% (Wang et al, 2020).…”
Section: Uses Of Contaminated Iris Sp Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomass valorization depends both on plant species used, type of pollutant and its concentration in plants (Vidican et al, 2020). Recent evidence emerged that I. sibirica Cobalt-rich biomass resulting from phytoremediation could be used in the domain of adsorption catalysis to remove Hg from coal combustion flue gas with highly promising industrial applications (Li et al, 2020;Wang et al, 2020). In this sense, results showed that after pyrolysis at 700°C, I. sibirica biochar achieved Hg removal efficiency of 85% (Wang et al, 2020).…”
Section: Uses Of Contaminated Iris Sp Biomassmentioning
confidence: 99%
“…Recent evidence emerged that I. sibirica Cobalt-rich biomass resulting from phytoremediation could be used in the domain of adsorption catalysis to remove Hg from coal combustion flue gas with highly promising industrial applications (Li et al, 2020;Wang et al, 2020). In this sense, results showed that after pyrolysis at 700°C, I. sibirica biochar achieved Hg removal efficiency of 85% (Wang et al, 2020). I. pseudacorus biomass resulting from biorefinery system used in removal of excess phosphate from water, could be valorized by obtaining flavonoid extract and compost.…”
Section: Uses Of Contaminated Iris Sp Biomassmentioning
confidence: 99%